Mengasihi Orang Miskin: Tinjauan Anjuran Surat Apostolik Paus Leo XIV Dilexi Te dan Relevansinya bagi Keberagaman di Indonesia - Agustinus Abraham (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to examine the theological meaning of love for the poor in the apostolic exhortation Dilexi Te and to reflect on its relevance within the context of Indonesia’s pluralistic society. The research employs a qualitative method with a literature study approach, using Dilexi Te as the primary source, supported by relevant theological and social literature. The findings reveal that love for the poor in Dilexi Te is not merely a charitable act but constitutes the core of Christian faith, inseparable from one’s relationship with God. This love is integral, encompassing spiritual, moral, and structural dimensions, and calls for active engagement in promoting social justice and addressing the root causes of poverty. Theologically, solidarity with the poor is grounded in the mystery of Christ’s incarnation and the principle of the preferential option for the poor. In the Indonesian context of diversity, this teaching holds strong relevance as a foundation for fostering interreligious solidarity, strengthening social cohesion, and encouraging both the Church and society to work toward a more just, inclusive, and humane social order. Therefore, this study highlights that theological reflection on love for the poor is not merely normative but also carries concrete social implications in a pluralistic society.